2020
DOI: 10.1007/s00038-020-01348-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists as youth-friendly service providers: documenting condom and emergency contraception dispensing in Kenya

Abstract: Objectives This Kenya-based study ascertained whether pharmacies were an untapped source of 'youth-friendly' health services by determining (1) whether young people (aged 18-24) could successfully obtain condoms and emergency contraception (ECP); (2) whether contraceptives were dispensed according to national guidelines; and (3) how young people felt about obtaining ECP and condoms from pharmacy personnel. Methods This study used several methods to capture and cross-check purchasing experiences as reported by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…Eleven studies were found from six countries that explored the service provision of pharmacy professionals in the sexual and reproductive health theme [ 18 , 21 , 22 , 23 , 24 , 48 , 66 , 67 , 68 , 69 , 70 ]. Sexually transmitted infections (STIs), including HIV/AIDS, and family planning were the primary targets of the interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies were found from six countries that explored the service provision of pharmacy professionals in the sexual and reproductive health theme [ 18 , 21 , 22 , 23 , 24 , 48 , 66 , 67 , 68 , 69 , 70 ]. Sexually transmitted infections (STIs), including HIV/AIDS, and family planning were the primary targets of the interventions.…”
Section: Resultsmentioning
confidence: 99%
“…In Kenya, this underreported subgroup of unmarried women with less recent sex exhibited similarly lower mCPR (current and at last sexual intercourse) and higher unmet need relative to their female counterparts–and is increasingly leveraging ECP access to prevent unwanted pregnancies. With ECP free in public health facilities and available without prescription at private pharmacies, approaches to further expand ECP uptake, such as targeted demand generation campaigns, may benefit this female subgroup in managing unintended pregnancies [ 27 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kenya has implemented policies to reduce barriers to access family planning, such as policies enacted in 2013 to effectively eliminate family planning user fees as well as other public outpatient costs [ 24 ]. ECP is free at public health facilities and available for purchase without prescription in private pharmacies [ 25 – 27 ]. Since the last DHS was conducted over seven years ago, other data sources are needed to investigate recent changes in family planning practices in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Pharmacies and drug shops are often preferred because of privacy concerns, convenience, fast service, and perceived youth-friendliness. 9 , 10 , 11 In a mixed-methods study in Kenya, young people identified pharmacies as a preferred option that afforded privacy without the prohibitive costs of private facilities; many young people were willing to pay more for private pharmacy services to access high-quality, private care, citing pharmacies’ consistent pricing as an added benefit. 10…”
Section: Introductionmentioning
confidence: 99%